The Leadership (Imamate) According to al-Juwayni in his Book Ghiyath al-Umam fi Iltiyath al-Zulam - Eid Al-Sarhan, Khader Eid Al-Sarhan; Alqudah, Ghadeer (Arts and Social Sciences Series, 2026)
This study examines the concept of Imamah in the thought of Imam al-Juwayni through his book Ghayath al-Umam fi Iltiyath al-Zulam, as one of the most important sources in the formation of Sunni political theory in the fifth century Hijri, within the context of the weakening of the Abbasid Caliphate and the rise of regional powers. The study aims to clarify the religious and intellectual foundations upon which al-Juwayni constructed his conception of Imamah, in terms of the conditions of the Imam, the methods of establishing the Imamah, the limits of his authority, as well as his position on the deposition of the Imam and rebellion against him. The research adopts a historical-analytical approach by examining al-Juwayni’s original texts and comparing them with the views of leading scholars of Islamic political jurisprudence before him. The study concludes that al-Juwayni presented a balanced conception that combines commitment to religious legitimacy with the requirements of political stability through his rejection of political vacuum and his formulation of precise regulations for deposing the Imam, which makes his theory of Imamah an advanced stage in the development of Islamic political thought.